Features reported after exposure to automatic dishwashing rinse aids. (June 2020) - Day, R; Bradberry, SM; Sandilands, EA; Thomas, SHL; Thompson, JP; Vale, JA
Introduction: Automatic dishwashing rinse aids are drying aids which contain non-ionic surfactants, usually ethoxylated alcohols, typically at concentrations of ≤30%. Objective: To assess the reported toxicity of rinse aids. Methods: Telephone enquiries to the UK National Poisons Information Service were analysed from January 2008 to June 2019. Results: Ingestion : Ingestion was involved in 976 cases and produced gastrointestinal features, coughing and central nervous system depression, particularly in young children. In those in whom the amount ingested was known, the majority (56%) of children <18 years and of adults (57%) ingested <50 mL of rinse aid. Although moderate or severe exposures (Poisoning Severity Score (PSS) ≥ 2) were uncommon, they occurred significantly ( p < 0.0008) more often in adults (9.0%) than in children (1.8%); however, three of the four adults with PSS ≥ 2 co-ingested other substances. Eye exposure : Ocular exposure was reported in 35 cases, of whom 29 developed features. Eye irritation ( n = 10, 28.6%) and eye pain ( n = 10, 28.6%) were reported most commonly, and three patients (8.6%) developed corneal abrasions (PSS 2). Dermal exposure : Thirty-four patients were exposed dermally, and six (17.6%) reported features, including rash, numbness, pruritus and burns (PSS 1). Conclusions: Overall, clinical features developed in 47% of patients exposed to rinse aids, but more severe features (PSS ≥ 2) were rare (<3%) following exposure by any route.